Skills, Aging, and Productivity: Evidence from Panel Data - Rainer Kotschy; Uwe Sunde (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The demographic change is one of the most important challenges for many developed economies in the twenty-first century. This paper examines the effect of workforce demographics and the distribution of skills on aggregated productivity and output. Population aging may lead to secular stagnation in developed economies. We provide estimates for an upper boundary of the skills-aging-elasticity that describes how much human capital is required to increase in order to offset negative effects of aging in the most favorable setting.
Keywords: J11; O47; J10; 330